Evaluation of Lightmix Mycoplasma macrolide assay for detection of macrolide-resistant Mycoplasma pneumoniae in pneumonia patients. (March 2019) - Wagner, K.; Imkamp, F.; Pires, V.P.; Keller, P.M.
Abstract: Objectives: Rapid detection of macrolide resistance–associated mutations in Mycoplasma pneumoniae is crucial for effective antimicrobial treatment. We evaluated the Lightmix Mycoplasma macrolide assay for the detection of point mutations at nucleotide positions 2063 and 2064 in the 23S ribosomal RNA (rRNA) gene of M. pneumoniae that confer macrolide resistance. Methods: Samples from 3438 patients with a respiratory tract infection were analysed by M. pneumoniae real-time PCR, and 208 (6%) of them were tested positive. In this retrospective study, 163  M. pneumoniae real-time PCR–positive samples were analysed by the Lightmix assay, and results were compared to targeted 23S rRNA sequencing. Results: Macrolide-resistant M. pneumoniae were found in 15 (9%) of 163 retrospectively analysed samples. The Lightmix assay showed a sensitivity of 100% (95% confidence interval, 78.2–100) and a specificity of 100% (95% confidence interval, 97.5–100) as the detected M. pneumoniae genotype (148 wild type and 15 non–wild type) was confirmed by 23S rRNA sequencing in all samples. Conclusions: The Lightmix assay is an easy-to-use and accurate molecular test that allows rapid determination of macrolide resistance in M. pneumoniae.